Modifikasi Kitosan dari Limbah Udang menggunakan Metode Gelasi Ionik - Nurfatihayati Nurfatihayati; Ahmad Fadli; Sunarno Sunarno; Allailus Syah Safara; Aulia Permatasari (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2023)
Chitin contained in shrimp shells can be used as raw material for making chitosan which is then reprocessed into nanoparticle-sized chitosan which has many benefits. This study aims to synthesize nanoparticle chitosan using the ionic gelation method and determine the effect of variations in the concentration of formic acid, sodium tripolyphosphate (TPP), chitosan, and the volume ratio of chitosan: TPP on particle characteristics, which include particle size, polydispersity index, zeta potential, particle morphology, and functional groups of particles. The first step for making nanoparticle chitosan is to make a chitosan solution using a magnetic stirrer. After that, the TPP solution at a certain volume ratio between chitosan: TPP was added to the chitosan solution. Stirring is carried out for 1 hour with a stirring speed of 1200 rpm. Furthermore, the nanoparticle chitosan was characterized by using Particle Size Analyzer (PSA), zeta potential analyzer, Scanning Electron Microscopy (SEM), and Fourier Transform Infra-Red (FTIR). The synthesis of nanoparticle chitosan using the ionic gelation method has been successfully carried out, obtaining a particle size of 464.4 nm, a polydispersity index of 0.214, a zeta potential of +0.48, and a cross-link of chitosan-TPP particles is formed.